Coping Strategies in Post-War Rural Mozambique - Tilman Brück (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2005)
This paper analyses post-war coping strategies by farm households in developing countries. The analysis is based on a portfolio model of activity choices in war-affected rural Sub-Saharan Africa. A case study using farm household survey data estimates the determinants of agricultural coping strategies in post-war Mozambique. Post-war coping strategies are expected to differ from pre- and mid-crisis coping strategies. War-affected households are forced to adopt very risky coping strategies that re-enforce their vulnerability. Households choose between market and non-market forms of exchange and even exit markets entirely. Post-war reconstruction policy should focus on re-capitalizing households and providing public goods.
Keywords: 330; agriculture; households; rural development; war; Mozambique; Africa